Optimalisasi Perencanaan Tata Ruang Daerah Pinggiran Kota Palembang yang Berkelanjutan - Irsan, Irsan; Utama, Meria; Idris, Akhmad (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 14 No 1 (2025), 2025)
The suburban area is basically an area known as both a city and a village at the same time. This area is generally influenced by the character of the city both physically and non-physically and on the other hand also has a village character, so that the suburban area receives the implications of the city's problems which are so complex in economically, socially and environmentally. The purpose of this research is to obtain government policies and regulations regarding the utilization of sustainable suburban spatial planning, especially in Palembang as well as formulating the concept. This research is a normative juridical study, with a data collection method using library research. The results of the first discussion, the concept of a sustainable city has been largely included in regional regulations, but the hope of making Palembang a sustainable city or even Kertapati as a sustainable suburban area will still be a long time to be realized. This sustainable development regulation emphasizes more on the government's obligations alone. Second, sustainable suburban development still has many obstacles such as, minimal green open space, inadequate educational facilities, affecting the human development index which is still limited. Weak engagement in community empowerment. The most extreme poverty in Kertapati sub-district throughout Palembang city. Kertapati is one of the most slum areas. Third, sustainable suburban development is full of values, requiring careful planning and supervision at all levels. It requires qualitative growth of every individual and society. Wilayah pinggiran kota pada dasarnya merupakan daerah yang dikenal sebagai wilayah kota dan desa secara bersamaan. Daerah ini umumnya terpengaruh oleh karakter kota baik fisik maupun non fisik dan memiliki karakter desa, sehingga wilayah pinggiran kota menerima implikasi problematika kota yang begitu kompleks secara ekonomi, sosial maupun lingkungan. Tujuan penelitian ini untuk mendapatkan kebijakan dan pengaturan pemerintah mengenai pemanfaatan tata ruang daerah pinggiran kota yang berkelanjutan, mendapatkan kendala pemanfaatan tata ruang daerah pinggiran kota Palembang yang berkelanjutan dan merumuskan konsep optimalisasi pemanfaatan tata ruang daerah pinggiran kota Palembang yang berkelanjutan. Penelitian ini adalah penelitian yuridis normatif, dengan metode pengumpulan data menggunakan library research. Hasil pembahasan pertama, Konsep kota berkelanjutan sebagian besar ada dalam peraturan daerah,  tetapi harapan untuk menjadikan Palembang sebagai kota berkelanjutan atau bahkan kertapati sebagai wilayah sub urban masih lama terwujud. Perda pembangunan berkelanjutan ini lebih menekankan pada kewajiban pemerintah semata. Kedua, Pembangunan pinggiran kota berkelanjutan masih banyak kendala seperti, minimnya RTH, fasilitas pendidikan kurang memadai, berpengaruh pada indeks pembangunan manusia yang masih terbatas. Lemahnya engagement pada pemberdayaan masyarakat. Kemiskinan paling ekstrem di kecamatan Kertapati Se kota Palembang. Kertapati termasuk wilayah paling kumuh. Ketiga, Pembangunan pinggiran kota yang berkelanjutan sarat nilai, membutuhkan perencanaan dan pengawasan yang seksama pada semua tingkat. Pembangunan itu menginginkan pertumbuhan kualitatif setiap individu dan masyarakat.